Method of synthesis of Pd – containing nanoparticles for electrocatalytic applications - E. A. Khristich; V. K. Khlebnikov; T. M. Buslaeva; L. I. Boguslavsky (Тонкие химические технологии, 2010)
Platinum metals and their compounds are now widely used as catalysts for water electrolysis and fuel cells. We propose a new approach to the synthesis of nanoparticles. As model experiment we realized synthesis of palladium diacetate nanoparticles of controlled size. As special condition for new phase grow was chosen far from equilibrium boundary between two liquids [2]. Under this condition gradient of chemical potential the water - tetrahydrofuran (THF) interface was a powerful regulating factor of the palladium diacetate (II) particle size.